205. PREDICTORS OF THE DIFFICULTY OF TRANSCERVICAL SUBCARINAL LYMPH NODE DISSECTION IN ESOPHAGEAL CANCER. (24th September 2022) - Furuke, Hirotaka; Fujiwara, Hitoshi; Konishi, Hirotaka; Shiozaki, Atsushi; Ohashi, Takuma; Shimizu, Hiroki; Arita, Tomohiro; Yamamoto, Yusuke; Morimura, Ryo; Ikoma, Hisashi; Kuriu, Yoshiaki; Kubota, Takeshi; et al.
Abstract: Transmediastinal radical esophagectomy (TME) is a new minimally invasive approach without thoracotomy. However, transcervical dissection of subcarinal lymph nodes (SCLN) is challenging. The shape or narrowness of the mediastinal space, especially around the aortic arch to tracheal bifurcation, may affect the difficulty. The present study aimed to clarify predictors for the difficulty of transcervical SCLN dissection. Patients who underwent TME between 2016 and 2019 were included (n = 126). Four indicators, the cervical angle, carina distance, aorta distance, and sternum distance, were defined as indicators of the mediastinal narrowness by 3D-CT. The relationship between the difficulty of the transcervical SCLN dissection and clinicopathological features, including the above indicators, were investigated. In a univariate analysis, the cervical angle (p = 0.023), aorta distance (p = 0.002), and middle thoracic tumor (p = 0.040) correlated with the difficulty. The median cervical angle (degree) and aorta distance (mm) were 15 and 33 in difficult cases, and 19 and 43 in easy cases, respectively. In a multivariate analysis, middle thoracic tumor (odds ratio: 3.28, p = 0.050) and a short aorta distance (odds ratio: 5, p = 0.036) were independent predictive factors. The cervical angle, aorta distance, and middle thoracic tumor may predict the difficulty of transcervical SCLN dissection. In difficult cases, transhiatal approach is essential for safe lymphadenectomy.